2017
DOI: 10.1016/j.hlc.2017.06.529
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Epicardial Adipose Tissue and High Risk Plaque Characteristics: A Systematic Review and Meta-Analysis

Abstract: Background--Epicardial adipose tissue (EAT) is hypothesized to alter atherosclerotic plaque composition, with potential development of high-risk plaque (HRP). EAT can be measured by volumetric assessment (EAT-v) or linear thickness (EAT-t). We performed a systematic review and random-effects meta-analysis to assess the association of EAT with HRP and whether this association is dependent on the measurement method used.Methods and Results--Electronic databases were systematically searched up to October 2016. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Furthermore, we evaluated the associations between cardiac adipose tissue and myocardial flow reserve, left ventricular ejection fraction, CAC score and 123 I-MIBG uptake, separately in the three groups ( Table 2 and (14) 37 (13) 37 (14) 0.99 14 (10) 15 (8) 13 (12) 0.68 24 h systolic blood pressure (mmHg) 126 (14) 123 (11) 132 (14) 0.06 136 (10) 136 (10) 138 (10) 0.47…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we evaluated the associations between cardiac adipose tissue and myocardial flow reserve, left ventricular ejection fraction, CAC score and 123 I-MIBG uptake, separately in the three groups ( Table 2 and (14) 37 (13) 37 (14) 0.99 14 (10) 15 (8) 13 (12) 0.68 24 h systolic blood pressure (mmHg) 126 (14) 123 (11) 132 (14) 0.06 136 (10) 136 (10) 138 (10) 0.47…”
Section: Resultsmentioning
confidence: 99%
“…Results from studies in type 2 diabetes and mixed populations (diabetes and non-diabetes) are conflicting. In the studies reporting an association between epicardial adipose tissue and coronary artery disease, including high risk plaque characteristics and CAC [13][14][15], it remains uncertain if the associations demonstrated are truly independent from traditional risk factors. We report a lack of association between cardiac adipose tissue and CAC score in persons with type 2 diabetes free of cardiovascular disease in line with results from a study in a mixed population (34% had diabetes) with suspected or known coronary artery disease (referred for clinically indicated invasive coronary angiography) [16].…”
Section: Cardiac Adipose Tissue and Coronary Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…23 Recent studies connected the epicardial adipose tissue with the presence of high-risk coronary plaques, defined as presenting one of the following features: low attenuation, positive remodeling, napkin ring sign, spotty calcifications; studies have also shown that patients with high-risk plaques present a larger volume of epicardial fat, compared to those with no high-risk plaques. 24,25 Pericoronary and periplaque fat Pericoronary adipose tissue, as a fragment of the total epicardial fat, is located in direct contact to the coronary artery wall and has pro-inflammatory properties through its paracrine effect and local release of inflammatory cytokines, which can trigger plaque formation, progression, vulnerabilization, and even rupture. 26 Pericoronary fat (PF) has also been associated with the presence of vulnerable coronary plaques, even after adjustment for obesity and smoking.…”
Section: Epicardial Fat On Severity Of Cad and Plaque Vulnerabilitymentioning
confidence: 99%
“…Based on the anatomic proximity of EAT to the arterial adventitia of coronary arteries, the "outside in" hypothesis of atherosclerosis has been recently launched, according to which EAT components may trigger vascular inflammation and plaque destabilization through paracrine and vasocrine mechanisms. [9][10][11][12][13] It has been demonstrated that the amount of EAT is directly correlated with both the length and the severity of coronary lesions, at the same time being associated with the transformation of atherosclerotic plaques into a vulnerable phenotype, considered to be "high risk" for major cardiovascular events. 11 In a large study conducted by Nerlekar et al, a strong correlation was found between several CT features of vulnerable atherosclerotic plaques, such as low-attenuation lesions and positive remodeling at the lesion site.…”
mentioning
confidence: 99%